2018
DOI: 10.1146/annurev-immunol-042617-053028
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Alternative Adaptive Immune Systems in Vertebrates

Abstract: Adaptive immunity in jawless fishes is based on antigen recognition by three types of variable lymphocyte receptors (VLRs) composed of variable leucine-rich repeats, which are differentially expressed by two T-like lymphocyte lineages and one B-like lymphocyte lineage. The T-like cells express either VLRAs or VLRCs of yet undefined antigen specificity, whereas the VLRB antibodies secreted by B-like cells bind proteinaceous and carbohydrate antigens. The incomplete VLR germline genes are assembled into function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 121 publications
1
89
0
Order By: Relevance
“…We have recently reported that the sea lamprey, Petromyzon marinus, generates a broad repertoire of anti-glycan antibodies in response to immunization with a variety of cell lines and biological tissues (McKitrick et al, in review). In contrast to the gnathostomes which produce antibodies made of immunoglobulin domains, the agnathans or jawless vertebrates, utilize a class of proteins constructed with leucine rich repeat motifs called Variable Lymphocyte Receptors (VLRs) as antigen receptors (Pancer et al, 2004;Alder et al, 2005Alder et al, , 2008Boehm et al, 2018). These single-chain antibodies are produced and secreted by the VLRB lymphocyte lineage, and several groups have discovered and characterized monoclonal VLRB proteins that are specific for distinct carbohydrate structures (Han et al, 2008;Hong et al, 2013;Luo et al, 2013;Collins et al, 2017).…”
Section: Plant Lectins and Antibodies As Essential Tools For Probing mentioning
confidence: 99%
“…We have recently reported that the sea lamprey, Petromyzon marinus, generates a broad repertoire of anti-glycan antibodies in response to immunization with a variety of cell lines and biological tissues (McKitrick et al, in review). In contrast to the gnathostomes which produce antibodies made of immunoglobulin domains, the agnathans or jawless vertebrates, utilize a class of proteins constructed with leucine rich repeat motifs called Variable Lymphocyte Receptors (VLRs) as antigen receptors (Pancer et al, 2004;Alder et al, 2005Alder et al, , 2008Boehm et al, 2018). These single-chain antibodies are produced and secreted by the VLRB lymphocyte lineage, and several groups have discovered and characterized monoclonal VLRB proteins that are specific for distinct carbohydrate structures (Han et al, 2008;Hong et al, 2013;Luo et al, 2013;Collins et al, 2017).…”
Section: Plant Lectins and Antibodies As Essential Tools For Probing mentioning
confidence: 99%
“…The thymus produces multiple T cell types that play key roles in both innate and adaptive immune responses. The importance of these responses has now been shown in sister lineages of vertebrates, long after the function of the thymus was proven for jawed vertebrates in the 1960s [1,2]. Indeed, a key feature of adaptive immunity lies in its ability to generate a wide diversity of antigen receptors that target non-self.…”
Section: Thymic Medulla and The Control Of T Cell Tolerancementioning
confidence: 99%
“…Even jawless fish such as lamprey have structures resembling a thymus and their genome encodes for various immune‐effector genes (eg, cytokines, relevant transcription factors) . While lymphocytes of jawless fish express variable lymphocyte receptors, somatically diversified antigen receptors composed of tandem arrays of leucine‐rich repeats, adaptive T and B cells equipped with antigen receptors generated by recombination of receptor gene elements first appear in jawed vertebrates . Since ILCs do not depend on recombined antigen receptors, it has been speculated that they are an evolutionary older branch of the lymphocyte family.…”
Section: Evolutionary Aspects and Outlookmentioning
confidence: 99%